(untitled) (Fiep Bulletin - online, 2014)
The reaction time represents the time needed to sense, evaluate a stimulus (sonorous or visual) and respond to it. It indicates the decision making speed and effectiveness. Although it is represented by a small time interval (milliseconds), on it many complex neuromuscular processes important to the movement control occur. The aim of this study was to verify is there is a significant difference in the simple visual reaction time (SVRT) before and immediately after a resistance training (RT) session. To evaluate the SVRT we used the software TTR. The sample was 37 individuals (23 male and 14 female), with a mean age of 26,3±9,9 years old. In the experimental group the test was executed before the beginning of the RT session and immediately after the execution of at least 5 resistance exercises of upper limbs. In the group that didn’t execute the RT (control group) the test was executed before and after six minutes of rest. The data analyzes was made with the statistic software SPSS 14.0. The descriptive statistic was used with a measure of central tendency and variability and the Wilcoxon test was used for the non parametrical data, by using a significance level of 5%. The median and the standard deviation of the SVRT in the experimental group , before and after the RT session (6 ± 1 exercises), were respectively 242,9 ± 50,4 ms and 223,5 ± 52,7 ms. In the control group it was 219 ± 59,5 ms and after the resting time (mean of 6 minutes) it was 223,1 ± 65,3 ms. The Wilcoxon test has shown a significant difference (p=0,04) between the SVRT values before and after the RT session (experimental group) and didn’t show significant difference (p=0,638) for the SVRT values in the control group.